Intra-population Variability for Grain Iron and Zinc Densities in Commercial Open-pollinated Varieties of Pearl Millet - Kanatti, A.; Radhika, K.; Padma, V.; Janila, P.; Govindaraj, M.; Rai, K. N. (International Journal of Economic Plants, 2015)
Intra-population variability using S1 progenies was studied for grain iron (Fe) and zinc (Zn) densities and 1000-grain weight in two released and commercial open-pollinated varieties (ICTP 8203 and ICMV 221) of pearl millet. Analysis of variance showed highly significant variability for all the traits in both populations. In ICTP 8203, Fe density varied from 44 to 76 mg kg-1 and Zn density from 40 to 60 mg kg-1; while in ICMV 221, Fe density varied from 40 to 78 mg kg-1 and Zn density from 31 to 52 mg kg-1. Higher broad-sense heritability was observed for both micronutrients in both populations (77% in ICTP 8203 and 86% in ICMV 221 for Fe; and 71% in ICTP 8203 and 72% in ICMV 221 for Zn). This substantial genetic variability coupled with high heritability implies good prospects for improvement of both populations for these micronutrients. The highly significant and high positive correlation observed between Fe and Zn densities (r=0.66 in ICTP 8203 and r=0.72 in ICMV 221, p<0.01), suggested that both micronutrients can be effectively improved simultaneously. Both micronutrients had non-significant or small positive correlation with 1000-grain weight, implying these can be improved in large-seeded genetic backgrounds.